Quantitative Analysis and Research on Flipped Classroom Teaching Method - Jieru, Zheng (International Journal of Management and Education in Human Development, 2022)
Education is an important way to improve the quality of the working population. To improve the teaching effect, people are actively exploring more effective teaching techniques. The flipped classroom teaching method is one of them. The research of this article is divided into two parts. The first part uses quantitative methods to analyze the learning effects of learners who use flipped classrooms. The second part uses the interview method to understand the learner's work situation, and to analyze whether the flipped classroom can improve the learner's workability. The results of the two parts of the research show that the flipped classroom has a positive role in improving the learning effect and working ability of learners. In the research, it is found that the flipped classroom has a certain guiding effect on the learner's choice of occupation.